Does Amount of Pre-cue Encoding Modulate Selective List Method Directed Forgetting? - Kliegl, Oliver; Pastötter, Bernhard; Bäuml, Karl-Heinz T. (Frontiers in Psychology, 2020)
Prior work reported evidence that when people are presented with both a relatively short list of relevant information and a relatively short list of irrelevant information, then a subsequent cue to forget the irrelevant list can induce successful selective directed forgetting of the irrelevant list without any forgetting of the relevant list. The goal of this study was to determine whether this selectivity effect is restricted to short lists of information (6 items per list), or whether the effect generalizes to longer lists (12 items per list). In Experiment~1, we replicated the finding that selective directed forgetting can arise when short lists of relevant and irrelevant information are employed. Going beyond this replication, we showed in Experiment~2 that such selectivity can arise both when shorter and when relatively longer lists of items are used. The results are consistent with the view that selective directed forgetting can result from the action of a flexible inhibitory mechanism. They are less well in line with the view that selective cues to forget precue information induce a change in partipants' mental context.